I live in fear [videorecording (DVD)] - Kurosawa, Akira, 1910-1998; Mifune, Toshiro, 1920-1997; Miyoshi, Eiko; Shimura, Takashi, 1905-1982; Chiaki, Minoru, 1917-1999 (Eclipse (Criterion Collection (Firm)). Postwar Kurosawa., 2007)
An elderly and wealthy industrialist is driven to madness over fears of a nuclear attack. In a futile attempt to save his family he pressures them to leave Japan and move to the rain forest in Brazil where he believes they will be safe. His family, complacent and cynical, is outraged and move to have him declared insane.